The Speech Surrogacy Systems of the Yoruba Dùndún and Bàtá Drums. On the Interface Between Organology and Phonology - González, Mariano; Oludare, Olupemi (Frontiers in Communication, 2022)
This paper explores the interdependence between organology and phonology in the Yoruba dùndún and bàtá drums. We analyze how the specific features of these drums, such as corpus shape, size, kind and number of membranes, and playing techniques affect their systems of speech surrogacy. The study relies on field recordings collected by the authors in Lagos, Nigeria, in February 2020, featuring drummed performances of Yoruba sentences previously unknown to the informants. The recorded sentences were transcribed and analyzed comparatively, which allows us to characterize systematic regularities in the speech-to-drum mapping. Observing how the intrinsic characteristics of language sounds (pitch, duration, intensity and spectrum) are addressed by means of the organologic and acoustic properties of the dùndún and the bàtá, we conclude that these drums’ different properties foster distinct speech surrogacy systems. Alongside a consideration of native perspectives on speech surrogacy, we propose an understanding of drum languages as platforms capable of supporting the development of native theories on sound and language.